A Mathematical Model Captures the Structure of Subjective Affect. (May 2017) - Mattek, Alison M.; Wolford, George L.; Whalen, Paul J.
Although it is possible to observe when another person is having an emotional moment, we also derive information about the affective states of others from what they tell us they are feeling. In an effort to distill the complexity of affective experience, psychologists routinely focus on a simplified subset of subjective rating scales (i.e., dimensions) that capture considerable variability in reported affect: reported valence (i.e., how good or bad?) and reported arousal (e.g., how strong is the emotion you are feeling?). Still, existing theoretical approaches address the basic organization and measurement of these affective dimensions differently. Some approaches organize affect around the dimensions of bipolar valence and arousal (e.g., the circumplex model), whereas alternative approaches organize affect around the dimensions of unipolar positivity and unipolar negativity (e.g., the bivariate evaluative model). In this report, we (a) replicate the data structure observed when collected according to the two approaches described above, and reinterpret these data to suggest that the relationship between each pair of affective dimensions is conditional on valence ambiguity, and (b) formalize this structure with a mathematical model depicting a valence ambiguity dimension that decreases in range as arousal decreases (a triangle). This model captures variability in affective ratings better than alternative approaches, increasing variance explained from 60% to over 90% without adding parameters.